Isolated Primary Diffuse Large B-Cell Lymphoma of Mandible – a Case Report with Its Valuable Diagnostic Work-up - Sanket Vakharia; Seema Gupta; Parag Watve (Research Highlights in Disease and Health Research Vol. 2, 2023)
Non-Hodgkin’s lymphoma [NHL] are a group of neoplasms that originate from the cells of the lymphoreticular system. Non-Hodgkin’s lymphomas detected primarily in the bone of head and neck region are quite rare, with isolated mandibular NHL accounting for 0.6% of all NHLs. In this localization, the clinical features & the radiologic appearances are not pathognomic and can pose significant diagnostic problems. Therefore, a detailed clinical evaluation as well as histopathological and immunohistochemical analysis are mandatory to enable accurate diagnosis. Primary diffuse large B-cell lymphoma of the bone can be effectively managed by chemotherapy, with or without radiotherapy. Here we report a case of a diffuse large B-cell lymphoma of the mandible, in which the patient presented with a mass on the middle one-third of mandible. A subsequent biopsy and immunohistochemistry played a key role in the diagnosis. After finding no metastasis to other sites, the patient was treated with chemotherapy.